Strategi Pelembagaan Nilai Pancasila Dalam Konteks Konstitusionalisme - Yamin Yamin (Jurnal Ketahanan Nasional, 2012)
In this paper a strategy elaborated in the context of the institutionalization of Pancasila (five principles of state) values of constitutionalism. Instituted before the Pancasila, the concepts and precepts contained in every principle between concepts need to be identified. Institutionalization in the context of constitutionalism essentially are attribution of power to state institutions (certain) and prescription authority mandates. In addition, this paper also shows that the institutionalization of the Pancasila traces recorded in legal documents from time to time, starting time of the old order, new order era, to the contemporary era is often called the era of reform. Taking into consideration the institutionalization of the Pancasila in the context of constitutionalism in the past and its development strategy should be formulated institutionalization.